2019
DOI: 10.11114/jets.v7i3.3902
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Pre-Service Teachers’ Competencies in Lesson Planning

Abstract: This study concerns the investigation of pre-service teachers’ competencies in lesson planning from different perspectives. In this respect, it is intended to develop a roadmap to figure out the pre-service teachers’ competency levels in lesson planning pertaining to a four-year- education program. The study was designed as a quantitative study and the general screening model was used. This model is designed with the relational screening model. The study population comprises of 3rd grade and senior students ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…This result is consistent with Süral (2019), who developed a roadmap to figure out the lesson planning competency levels of pre-service teachers in a four-year education program. Considering the reliability and validity levels, this scale can also be administered to different sample groups.…”
Section: Discussionsupporting
confidence: 88%
“…This result is consistent with Süral (2019), who developed a roadmap to figure out the lesson planning competency levels of pre-service teachers in a four-year education program. Considering the reliability and validity levels, this scale can also be administered to different sample groups.…”
Section: Discussionsupporting
confidence: 88%
“…In addition to be a broad concept, the term 'competence' or 'competency' is quite new in education and still used as an equal standard (Mayer et al, 2005;Peklaj, 2015;Centre of Study for Policies and Practices in Education, 2000;Sural, 2019;Torrance & Forde, 2017). On the other hand, 'competence' has obtained a growing reputation in diverse academic disciplines, and now much supported in universities aiming at producing competent and prepared graduates for the job (Lester, 2014;O'reilly et al, 2013).…”
Section: Teacher Competencementioning
confidence: 99%
“…Nevertheless, the results of the study conducted by Çubukçu and Girmen (2008) revealed that the female teachers, in comparison to the male teachers, attached more significance to planning the teaching process in classroom management and tended to work more systematically. Similarly, the results of the study conducted by Süral (2019), Çetin and Çetin (2019) revealed a significant difference in favor of female pre-service teachers regarding the attitudes of male and female pre-service teachers towards lesson planning instruction.…”
Section: Discussionmentioning
confidence: 81%